Synthesis and Characterization of Hydrogel from Gongronema latifolia for Potential Drug Delivery - J, Amadi I.; B, Attah Daniel E.; J, Ugye T.; S, Ikpatim; J., Aasegh T. (African Journal of Clinical Medicine and Pharmacy Research, 2026)
This study reports the synthesis and characterization of a plant-based hydrogel derived from Gongronema latifolium leaf extracts for potential drug delivery applications. Bioactive components, including alkaloids, flavonoids, terpenoids, and saponins, were extracted from the leaves using standard procedures, after which a biocompatible hydrogel was synthesized from poly(vinyl alcohol) (PVA) and polyethylene glycol (PEG) and characterized using UV–visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and X-ray diffraction (XRD). The results confirmed the successful incorporation of the plant extracts, revealing a porous, interconnected three-dimensional polymer matrix. TGA data showed that the hydrogel is thermally stable, bioactive, and possesses semicrystalline porous structures with high entrapment capacity, making it suitable for drug delivery, water retention, and solute diffusion. FTIR analysis confirmed the presence of hydroxyl, carbonyl, and other functional groups, indicating strong hydrogen bonding and extensive polymeric crosslinking. SEM images revealed a rough, heterogeneous surface morphology with interconnected pores, while XRD patterns indicated slight crystalline features within an overall amorphous structure. Collectively, these findings demonstrate the successful development of a structurally robust and bioactive hydrogel with promising applications in drug delivery and agriculture. The hydrogel’s properties position it as an attractive alternative to synthetic petrochemical-based materials that pose environmental risks and highlight the potential of Gongronema latifolium leaf-extract-based hydrogels for future therapeutic and drug delivery applications.